Small scale industries and India's economic development - "Tarun , Tara Nand Singh" (New Delhi, 1986)
India as a new corner to the comity of independent nations started its governance with a body of experienced leaders, an organised administrative set up based largely on Anglo-Saxon principles. The inauguration of the Republic of India on January 26, 1950 which was the culmination of the transfer of central authority to India in 1858 and founding of the Indian National Congress in 1885 unleashes tremendous scope of economic revival through small scale industries which came to be identified as the core sector for making an economic thrust for the upliftment of rural poor.-
Keywords: Economics development